The effect of the emerging omicron variant on the willingness to take or continue with COVID-19 vaccination in the Middle East - Tareq L. Mukattash, Anan S. Jarab, Rana K. Abu-Farha, Rania Itani, Samar Karout, Razan Z. Mansour, Shorouq Abuhishmah (Journal of Applied Pharmaceutical Science, 2022)
The present study aimed to explore the willingness of the general public in the Middle East area to take or continue with the available COVID-19 vaccine in light of the emergence of the new omicron variant. This study is a web-based questionnaire distributed in Lebanon, Jordan, and Kuwait during the omicron variant outbreak. The questionnaire consisted of 15 close-ended questions with predefined options, divided into four sections preceded. The total included responses were 812 that were recruited from Lebanon (n= 427, 52.6%), Jordan (n = 279, 34.4%), and Kuwait (n = 106, 13.1%). Almost two-thirds of the participants (77%) received two doses of the COVID-19 vaccine, while only 7.9% received the booster shot (third dose). On the other hand, 90 participants (11%) did not receive any COVID-19 vaccine yet. The reported willingness among the unvaccinated individuals to receive the COVID-19 vaccine was only 22.4% (20/90). However, higher acceptability of fully vaccinated individuals to receive the booster shot was reported after the surge of the omicron variant (49.2%). The findings of the present study have important implications on COVID-19 vaccination decision. As the pandemic evolves, the public’s opinions with the surge of different variants are changing. Therefore, there is an urgent need to raise awareness about omicron severity, and that the rapidly spreading strain puts the unvaccinated particularly at risk. Vaccine campaigns should elevate the voices of influencing messengers caring for severe COVID-19 cases.
Keywords: COVID-19, vaccine, omicron, willingness, Middle East